Antimicrobial and Antihelminthic Activities of Various Extracts of Leaves and Stems of Abutilon indicum Linn - Madan Ranjit, Pusapati (International Journal of Pharmaceutical & Biological Archive, 2013)
Antimicrobial and Antihelminthic Activities of Various Extracts of Leaves and Stems of Abutilon indicum Linn